2009
DOI: 10.1080/10874200902885852
|View full text |Cite
|
Sign up to set email alerts
|

EEG Asymmetry Analysis of the Left and Right Brain Activities During Simple versus Complex Arithmetic Learning

Abstract: Introduction. Repeated practice of simple arithmetic such as addition, subtraction, and multiplication has been widely used for effective math education. Brain activity patterns during simple and complex arithmetic calculation have been explored by several research groups using magnetic resonance images (MRI) and functional MRI (fMRI), and some have reported that the balanced whole brain (both left and right brain) activities during simple arithmetic in contrast to the predominant left brain activities during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…These findings yielded some interesting metrics, called ratios, to measure and express mental operations. Thus, recent work in asymmetry analysis relevant to our research has revealed higher Beta asymmetries from the left brain during complex arithmetic processes compared to simple computations [63]. This area of research can potentially be quite invaluable in accessing whether the learner is engaged in far too much mental arithmetic than required for a specific lesson.…”
Section: Background On Eegmentioning
confidence: 62%
“…These findings yielded some interesting metrics, called ratios, to measure and express mental operations. Thus, recent work in asymmetry analysis relevant to our research has revealed higher Beta asymmetries from the left brain during complex arithmetic processes compared to simple computations [63]. This area of research can potentially be quite invaluable in accessing whether the learner is engaged in far too much mental arithmetic than required for a specific lesson.…”
Section: Background On Eegmentioning
confidence: 62%
“…Since the inception of mobile technology, devices have evolved into small and powerful computing devices that connect directly to public networks to provide and use Internet applications and services. Wireless technologies, such as Universal Mobile Telecommunications System (UMTS-3G) and High-Speed Downlink Packet Access (HSDPA-3.5G), wireless fidelity (Wi-Fi), and Worldwide Interoperability for Microwave Access (WiMAX) [2], have converged into a common IP network [3] and this has made it much easier for devices to interconnect and interoperate with each other. One domain exploring the use of such technologies is healthcare were new medical applications are being designed to optimize and deliver better healthcare services [4].…”
Section: Wireless Healthcarementioning
confidence: 99%
“…Once they connect to the network, they can immediately offer and use services provided by other devices within their locale. Based on the flexibility Bluetooth provides it has been implemented in a number of different systems, i.e., hands free, game controllers, biofeedback and neurology (NeXUS-10) [2], and gait analysis systems (XSens) [3], to name a few.…”
Section: Personal Area Communicationsmentioning
confidence: 99%
See 2 more Smart Citations